Emmy and the rats in the belfry - Jonell, Lynne; Bean, Jonathan (New York : Henry Holt, 2011)
Ten-year-old Emmy and her rodent friends must fend off the evil former nanny, Miss Barmy, as they search for Ratty's missing mother.
Keywords: Rodents -- Juvenile fiction; Rodents -- Fiction; Rats -- Fiction; Nannies -- Fiction; Talking animals -- Fiction; Transformations(Magic) -- Fiction; Revenge -- Fiction; Ten-year-old girls -- Fiction; Addison, Emmy(Fictitious character) -- Fiction; Fantasy; Humorous stories